2023
DOI: 10.3390/gels9050423
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Surface Modification of Titanium Implants by Hydrogel Coatings

Abstract: Although titanium and titanium alloys have become the preferred materials for various medical implants, surface modification technology still needs to be strengthened in order to adapt to the complex physiological environment of the human body. Compared with physical or chemical modification methods, biochemical modification, such as the introduction of functional hydrogel coating on implants, can fix biomolecules such as proteins, peptides, growth factors, polysaccharides, or nucleotides on the surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…Owing to the adjustability of the intercommunicating networks of hydrogels, they are attractive for loading antibacterial agents with various molecular weights and physiochemical properties and sustaining their release around the implantation site [ 25 , 28 ]. Among the biopolymers used in the formation of hydrogels, biologically relevant materials, including collagen, gelatin, hyaluronic acid, chitosan, and alginate, are widely used owing to biodegradability, safety, and their capabilities of inducing cell adhesion, growth, and differentiation [ 28 , 81 , 82 ]. Among previous studies, Wu et al [ 83 ] reported on utilizing binary combinations of chitosan and gelatin for producing hydrogel coatings on Ti implants, facilitating bone cell adherence and growth.…”
Section: Biofilm Formation On Orthopedic Implants and Prevention Stra...mentioning
confidence: 99%
“…Owing to the adjustability of the intercommunicating networks of hydrogels, they are attractive for loading antibacterial agents with various molecular weights and physiochemical properties and sustaining their release around the implantation site [ 25 , 28 ]. Among the biopolymers used in the formation of hydrogels, biologically relevant materials, including collagen, gelatin, hyaluronic acid, chitosan, and alginate, are widely used owing to biodegradability, safety, and their capabilities of inducing cell adhesion, growth, and differentiation [ 28 , 81 , 82 ]. Among previous studies, Wu et al [ 83 ] reported on utilizing binary combinations of chitosan and gelatin for producing hydrogel coatings on Ti implants, facilitating bone cell adherence and growth.…”
Section: Biofilm Formation On Orthopedic Implants and Prevention Stra...mentioning
confidence: 99%
“…Also, they have a high absorption rate; therefore, films, sponges, and hydrogels can be manufactured using chemical or green chemical syntheses. Chitosan found applications in many domains such as in treatments for obesity [ 21 ], for dentistry [ 28 ], in drug delivery for improved encapsulation [ 29 ], in soft tissue engineering as gels for regeneration of skin or epithelium reconstruction [ 30 , 31 ] and in antibacterial applications together with AgNPs [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total hip arthroplasty surgery is an important method for treating joint diseases such as avascular necrosis of the femoral head. 6,7 Friction occurs between the artificial femoral head and the original acetabulum, leading to bone damage and inflammation. Hydrogel coatings applied on the surface of the artificial femoral head can effectively reduce friction and provide antibacterial properties, thereby extending the lifespan of the artificial joint.…”
Section: Introductionmentioning
confidence: 99%